Alquimia do ser : processos educativos estéticos em busca do equilíbrio biopsicoespiritual - Gallina, Franciele Silvestre (2012)
The theme area of this study consisted in the observation of transformations experienced in an esthetic education workshop developed with a group of women searching for self-knowledge to help them in the decision-making process. Linked with the Educative Processes and Language research, the problematic was represented by the following question: what is the meaning of an esthetic education workshop based on essential anthropology? The objective was to answer to this question by investigating such meaning with a group of women searching for biopsycho- spiritual balance. Through specific goals, it was defined: to study the theory of Jean-Yves Leloup proposed in the work O corpo e seus símbolos: uma antropologia essencial (1998) (The body and its symbols: an essential anthropology), also considering Merlau-Ponty theory in Fenomenologia da percepção (1999) (Phenomenology of perception), as well as from other authors; to observe the universe of embodiment in a triad of listening to body parts, from the physical, mental, and spiritual point of view; and to develop esthetic activities theoretically supported by essential anthropology to comprehend the personal and group transformations of the participants of the esthetics education workshop. The instruments were made from observations registered in the field diary of the researcher and from participants written testimonials. To understand the information, a phenomenological method proposed by Giorgi (1985) and Comiotto (apud ORMEZZANO; TORRES, 2003) was used. From the method application the following essences and dimensions emerged: 1) The individual who feels and cares: self knowledge and care; Care for others and the Universe; Emotions and feelings of the individual; 2) The individual who transforms: intelligible and sensitive educative experiences; The meaning of everyday life; The search for conscience; 3) The individual who transcends: where sacred meets education; Vibrational and energetic field; Symbolic language: Mythos and Logos.